Comparative and international education : survey of an infinite field - Wolhuter, C. C.; Wiseman, Alexander W. (International perspectives on education and society ;, 2019)
The scope and breadth of the field of comparative and international education is vast. In fact, there are few, if any, limitations on theme, method, or data in the field of comparative and international education. Every context or combination of contexts are available for comparative education scholars to scrutinise. The scope of this field brings both serious interest but also great challenges.This book explores the evolution and current state of the scholarly field of comparative and international education over 200 years of development. Experts in the field explore comparative and international education in each of the major world regions including Latin America, North America, Western Europe, Eastern Europe, the Middle East-North Africa, Oceania, South Asia, South-East and East Asia, and Sub-Saharan Africa.Illuminating studies conducted in the fields of higher education, teacher education, vocational education, and peace education shed light on the rise of global testing culture and take a closer look at the history of the region in relation to educational practice.This important text is the first to respond to the challenges currently facing comparative education on a multi-national scale and will prove invaluable for researchers in the field of global education.